Graficzne i fonetyczne warianty techniczne w polskiej edycji Żywotów filozofów Mikuláša Konáča (F. Ungler, Kraków 1535) - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
The article attempts the technical determination of the graphic and phonetic variance acknowledged in the Polish edition of the Żywoty filozofów by Mikuláš Konáč. The method used was to analyze the distribution of oppositional graphic forms. It has been determined that the technical nature of the print is 9 variants: 4 graphic variants („j” = /j/ in position before consonant, „j” = /j/ in the voice-over position, „u” = /v/ i /v/ in the midpoint position, „th” = /t/) and 5 phonetic variants (miesce, miejsce, miejstce; wszystko; wieliki); among them are both regressive and progressive forms. The analysis also shows that, using the disclosed technical variants, zecer manipulated the graphical content of the lines in both possible ways: narrowing or widening.